2017
DOI: 10.1016/j.ultsonch.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high power ultrasonic vibration on the cold compaction of titanium

Abstract: Titanium has widely been used in chemical and aerospace industries. In order to overcome the drawbacks of cold compaction of titanium, the process was assisted by an ultrasonic vibration system. For this purpose, a uniaxial ultrasonic assisted cold powder compaction system was designed and fabricated. The process variables were powder size, compaction pressure and initial powder compact thickness. Density, friction force, ejection force and spring back of the fabricated samples were measured and studied. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Fartashvand et al 17 investigated the influence of ultrasonic vibration on green part density, friction stress on die wall, and removal force of part from the die and found that ultrasonic vibration has an improving role in these parameters. Abedini et al 8 investigated the contribution of pressure, temperature, and high-power ultrasonic vibration on hot pressing of titanium alloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fartashvand et al 17 investigated the influence of ultrasonic vibration on green part density, friction stress on die wall, and removal force of part from the die and found that ultrasonic vibration has an improving role in these parameters. Abedini et al 8 investigated the contribution of pressure, temperature, and high-power ultrasonic vibration on hot pressing of titanium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…First, to investigate its effect on the properties of the green sample in cold compression, which was presented in our previous study. 17 This study determined the influence of ultrasonic vibration on sintered specimens’ density, shrinkage, and compression strength. Also, the effect of compaction load, aspect ratio, and powder size on mentioned properties was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The use of ultrasonic vibration in metal forming began in 1955 when Blaha and Langenecker applied ultrasonic vibration to tension tests of zinc single crystal and found that the flow stress of the material was significantly reduced [1]. Owing to the great advantages of ultrasonic vibration, many scholars have applied it in many metal forming processes and found that ultrasonic vibration can decrease stress [2][3][4], promote deformation [5][6][7][8], minish friction between workpiece and tool [9], and refine grain size [10], etc. In this paper, ultrasonic vibration-assisted compression (UAC) tests were conducted on Ti45Nb alloy, and the deformation behavior and mechanism were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported that the powder compaction is improved by decreasing the friction of powder caused by ultrasonic vibration [1][2][3] . Generally, the powder compaction is performed with ultrasonic vibration as well as high static pressure.…”
Section: Introductionmentioning
confidence: 99%